The stresses of veterinary training and significant intimate relationships: implications for the practice of marriage & family therapists - Nelsen, Teresa M. (Kansas State University, 2006)
Until recently, minimal research has been done regarding the impact of veterinary student stress on the student’s significant intimate relationships. In this study of 466 veterinary students enrolled in five different accredited U.S. Colleges of Veterinary Medicine, the association of five primary variables, perceived stress, self-esteem, academic satisfaction, relationship satisfaction, and general life satisfaction was investigated, utilizing McCubbin and Patterson’s (1983) Double ABCX Model as a guide. Six of the seven hypotheses were supported and further regression analysis yielded a model of variable associations that supported the Double ABCX Model, though significant gender differences were found. Specifically, female students perceived significantly more stress than did male students. With the exception of academic satisfaction and relationship satisfaction, all of the major variables were strongly correlated with each other. For the women, who comprised a significant majority of the sample, perceived stress had a significant impact on relationship satisfaction, as well as on self-esteem, which in turn significantly impacted academic satisfaction. Relationship satisfaction and academic satisfaction both significantly, and separately, impacted general life satisfaction, suggesting that relationship satisfaction and academic satisfaction are different constructs that operate independently of each other. However, both have a significant impact upon and are significantly associated with general life satisfaction, suggesting that neither can be neglected during veterinary training if a positive outcome is desired. For the men in this sample, stress impacted directly upon academic satisfaction, self-esteem, and general life satisfaction but did not have a direct impact upon relationship satisfaction. Instead, relationship satisfaction and general life satisfaction had a highly correlated relationship, with both significantly and strongly associated with the other. Although academic satisfaction and relationship satisfaction appear to be two separate entities, they are both important elements to achieving general life satisfaction during veterinary training and, therefore, should be equally attended to during the training process. These findings are interpreted and discussed in light of the implications for and importance of continued collaboration between veterinary students and programs and the field of Marriage and Family Therapy in an effort to understand and support students and their significant relationships during the veterinary training process.
Keywords: Marriage & Family Therapy; Veterinary Medicine; Biology, Veterinary Science (0778); Psychology, Clinical (0622)